2014
DOI: 10.7314/apjcp.2014.15.17.7277
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study on Carboplatin for Treating Pediatric Patients with Wilms Tumors

Abstract: According to this background, we hypothesize that carboplatin originated regimen could be established as an optimal schedule for treating pediatric patients with WT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Currently, several researches reported that the toxicity of carboplatin-based treatment was relatively low and unapparent. [36,37] Therefore, it was speculated that gemcitabine was more likely to cause the toxic effects of the carboplatin + gemcitabine chemotherapy regimen. Besides, current researches still cannot reach agreement on the toxic effects of gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several researches reported that the toxicity of carboplatin-based treatment was relatively low and unapparent. [36,37] Therefore, it was speculated that gemcitabine was more likely to cause the toxic effects of the carboplatin + gemcitabine chemotherapy regimen. Besides, current researches still cannot reach agreement on the toxic effects of gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…PC is a relatively common first-line chemotherapy regimen. Carboplatin, a commonly used adjuvant with acceptable toxicities, has shown great efficacy in combination therapy [32]. Pacilitaxel promotes stable microtubule assembly by acting specifically at the beta-tubulin subunit N-terminus [33], impeding depolymerization and inhibiting cancer cell division [9].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of WT is unclear and may be related to mutations in genes that regulate normal embryonic development of the urogenital tract ( Stock et al, 2002 ; Fukuzawa and Reeve, 2007 ). Most patients have a palpable abdominal mass as the first symptom, and some patients may present with symptoms of hematuria, fever, urinary tract infection, varicocele, and anemia ( Zhang et al, 2014 ). Currently, WT is treated with a multidisciplinary combination of surgical, chemotherapy, radiotherapy, and targeted therapy, with an overall cure rate of approximately 90% ( Anvar et al, 2019 ; Palmisani et al, 2021 ; Pelosi et al, 2021 ).…”
Section: Roles and Significance Of Circrnas In Pediatric Malignant Solid Tumorsmentioning
confidence: 99%